Reading Abbas: A Postcolonial Study of One of the Main Characters of Kelas Internasional - Anggun Putri Fatahillah (Passage, 2018)
Kelas Internasional, an Indonesian TV series depicting the dynamics of a class consisting of students of different nationalities, has a Nigerian character named Abbas, who is the only African student in the story. It is quite uncommon in Indonesian films to have an African playing as the main character; this study thus aims to analyze how the African character Abbas is represented in the TV series Kelas International. Adopting a qualitative descriptive method, the study draws on Hall’s (1997) theory of representation, Said’s (1979) Orientalism, and Doh’s (2009) stereotyping Africa to delve into the representations of Abbas. The study also employs Heintz and Stracey’s (2008) film theory, focusing primarily on the elements of mise en scène and the soundtracks, to understand how the representation of Abbas is constructed through film elements. The data analysis reveals that the character Abbas is primarily represented in a negative light: being educationally backward, economically poor, and attitude-wise impolite. This study indicates that Kelas Internasional tends to perpetuate negative stereotypes about Africans, rather than counter them. This study is expected to not only contribute to the field of postcolonial studies, but more importantly to raise Indonesian people’s critical awareness of implicit messages embedded in literary works. Keywords: postcolonial study, representation, African stereotypes, Indonesian TV series